Analisis Permasalahan Batas Darat Antara Indonesia dan Malaysia dalam Perspektif Aspek Teknis dan Teknologi Geospasial - Sukanto Hadi (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2022)
The implementation of survey boundary demarcation between Indonesia and Malaysia in Kalimantan has been carried out since 1975, and until now there are still 7 unresolved boundary issues. It’s called Outstanding Boundary Problems (OBP). In practice, issues arise due to differences in the datum and differences in the interpretation of the treaties of 1891, 1915, and 1928 between the Dutch Government and the British Government. This research aims to find an alternative model for the solution to the land boundary problem between Indonesia and Malaysia by conducting a critical, comprehensive study and analysis of the technical aspects of surveying and confirming the Indonesian and Malaysian state boundaries from the perspective of geospatial engineering and technology. This research combines an extensive literature study using maps, high-resolution satellite imagery, SRTM data, and field data from surveys and confirmation of the RI-Malaysia boundary to produce a comprehensive study from the perspective of technical aspects and geospatial technology. The results of the study resulted in an alternative model for solving land boundary problems between Indonesia-Malaysia, namely Indonesia received 3 claims and Malaysia obtained 3 claims from 7 existing problems and both parties divided the two for the Batu Aum area.